Slovene migrant literature in Australia - Maver, Igor (Acta neophilologica, 2002)
This article on the literary creativity of Slovene migrants in Australia after the Second World War, including the most recent publications, discusses only the most artistically accomplished authors and addresses those works that have received the most enthusiastic reception by the critics and readers alike. Of course, those that are not mentioned are also important to the preservation of Slovene culture and identity among the Slovene migrants in Australia from a documentray, historical, or ethnological points of view. However, the genres featured here include the explicitly literary, the semi-literary fictionalized biography, the memoir and documentary fiction, and the literary journalistic text - all those fields and genres that nowadays straddle the division line between 'high' literature and so-called 'creative fiction'.
Keywords: 1945/2000; 20.st.; Australia; Avstralija; avstralska književnost; Slovene literature; slovenska književnost; slovenski izseljenci; slovenski književniki